3D printed plates based on generative design biomechanically outperform manual digital fitting and conventional systems printed in photopolymers in bridging mandibular bone defects of critical size in dogs - Baumgartner, Doris; Schramel, Johannes Peter; Kau, Silvio; Unger, Ewald; Oberoi, Gunpreet; Peham, Christian; Eberspächer-Schweda, Matthias (Frontiers in Veterinary Science, 2023)
Mini-plate osteosynthesis of critical-sized bone defects in canine mandibles often fails to restore former functionality and stability due to adaption limits. Three-dimensional (3D) printed patient-specific implants are becoming increasingly popular as these can be customized to avoid critical structures, achieve perfect alignment to individual bone contours, and therefore provide better stability. Using a 3D surface model for the mandible, four plate designs were created and evaluated for their properties to stabilize a defined 3cm critical-size bone defect. Design-1 was manually designed, and further shape optimized using Autodesk® Fusion 360 (ADF360) to generate Design-2. Design-4 was created with the generative design (GD) function from ADF360 using preplaced screw terminals and loading conditions as boundaries. A regular 12-hole titanium locking plate (LP) (2.4/3.0mm) scanned and converted into a 3D printable format was also tested (Design-3). Each design was 3D printed from a photopolymer resin (VPW) and a photopolymer resin in combination with a thermoplastic elastomer (VPWT) and loaded in cantilever bending using a customized servo-hydraulic mechanical testing system; n=5 repetitions each. No material defects were found in the printed mandibles and screws/holes. Plate fractures were most often observed in similar locations, depending on the design. Design-4 has 2.8–3.6 times higher stability compared to other plates, even though only 40% more volume was used. Maximum load capacities did not differ significantly from those of the other three designs. Except for LPs (6%), VPW plates were 35% stronger compared to VPWT plates. Generative design takes less time than manual design and provides greater stability. It can also be used by non-professionals to design custom implants with maximum load-bearing capacity and minimum material requirements. Although guidelines for selecting appropriate outcomes and subsequent refinements to the optimized design are still needed, this may represent a straightforward approach to implementing additive manufacturing in individualised surgical care.